2020
DOI: 10.1002/pssr.201900701
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Behavior on Cesium Fluoride‐Treated Cu(In1–x,Gax)Se2 Solar Cells

Abstract: Metastable behavior of cesium fluoride (CsF)‐treated Cu(In1–x,Gax)Se2 (CIGS) solar cells is investigated under heat‐light soaking (HLS) and heat‐soaking (HS) treatments. HLS increases open‐circuit voltage, fill factor, efficiency, and net carrier concentration and decreases short‐circuit current density, whereas heat‐soaking treatment acts oppositely. The performance of a CsF postdeposition treatment to CIGS thin film in selenium vapor, and closer to stoichiometry copper content, did not mitigate the open‐circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Recently, chalcopyrite Cu(In,Ga)S,Se 2 (CIGSSe) thin‐film solar cells with air mass (AM) 1.5 conversion efficiency exceeded 23%, the highest value among the thin‐film solar cell technologies . These highest power conversion efficiency and high radiation tolerance show good potential for space application . Flight data demonstrate no degradation of Cu(In,Ga)Se 2 (CIGS) solar cell performance by proton irradiation and thermal annealing .…”
Section: J–v Parameters Of Csf‐free and Csf‐treated Cigs Solar Cells mentioning
confidence: 99%
“…Recently, chalcopyrite Cu(In,Ga)S,Se 2 (CIGSSe) thin‐film solar cells with air mass (AM) 1.5 conversion efficiency exceeded 23%, the highest value among the thin‐film solar cell technologies . These highest power conversion efficiency and high radiation tolerance show good potential for space application . Flight data demonstrate no degradation of Cu(In,Ga)Se 2 (CIGS) solar cell performance by proton irradiation and thermal annealing .…”
Section: J–v Parameters Of Csf‐free and Csf‐treated Cigs Solar Cells mentioning
confidence: 99%
“…chemical passivation [6,15], and 2) repelling minority carriers by a built-in electrical field due to fixed charges at the dielectric surface [16][17][18]. While this approach has been successfully implemented in the rear contact, the front contact has been mostly improved using alkali post deposition treatments [9,19,20], However, it is still heavily debated its full effects and if benefits are due to bulk recombination changes [21][22][23][24]. In PDT processes, after the CIGS deposition, a fluorine-alkali compound is evaporated on the CIGS, leading to several optoelectronic changes that improve device performance [23,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Cu(In,Ga)(S,Se) 2 or CIGS photovoltaic devices are a promising thin‐film photovoltaics (PV) technology with a record 23.4% cell and 19.2% module efficiency, respectively. [ 1 ] Alkali treatments (Na, [ 2–6 ] K, [ 6–10 ] Rb, [ 10–12 ] and Cs [ 11,13 ] ) are a crucial step toward attaining high efficiency devices with improved p‐type conductivity, [ 4,7,12–15 ] and grain boundary and interface passivation, [ 12,16–22 ] resulting in improved open‐circuit (OC) voltage ( V OC ). The increased p‐type doping in Na‐treated CIGS devices has been speculated to originate from many possible mechanisms such as the introduction of Na‐related acceptor defects, introduction of O Se deep acceptor defects, elimination of In Cu compensating donors or elimination of defects at grain boundaries, and surface passivation.…”
Section: Figurementioning
confidence: 99%
“…[ 27–35 ] A number of groups have reported an increase in V OC under light soaking which has been attributed to increase in apparent doping density. [ 4,7,13–15,34,35 ] Erslev et al [ 35 ] observed an increase in carrier density in Na‐containing devices after light exposure, but no increase in carrier density in Na‐free CIGS devices. Heise et al [ 36 ] recently reported a metastable decrease in current collection efficiency of CIGS solar cells in addition to a metastable increase in V OC after light soaking.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation